2016
DOI: 10.4049/jimmunol.1600077
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive CD40 Signaling Calibrates Differentiation Outcomes in Responding B Cells via Multiple Molecular Pathways

Abstract: CD40 signaling during B cell activation is known to inhibit terminal differentiation and promote memory generation. Blimp-1 is essential for efficient plasma cell (PC) generation, and although CD40 signaling is known to inhibit Blimp-1 induction during B cell activation, the mechanisms involved have been unclear. We report that CD40 signaling induces miR-125b that targets Blimp-1 transcripts, and increases amounts of the ubiquitin ligase Hrd1 that targets BLIMP-1 protein for proteasomal degradation. CD40 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…D40, a costimulatory receptor in B cells and one of the TNF receptor family members, is known to in uence the fate of B cells [48] . Previous studies have shown that CD40 signaling can stimulate B cell expansion and differentiation and its strength can regulate the development of various memory B cell subtypes [49][50][51] . Furthermore, aberrations in these driver genes have been widely demonstrated to cause hyperactivation of the PI3K signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…D40, a costimulatory receptor in B cells and one of the TNF receptor family members, is known to in uence the fate of B cells [48] . Previous studies have shown that CD40 signaling can stimulate B cell expansion and differentiation and its strength can regulate the development of various memory B cell subtypes [49][50][51] . Furthermore, aberrations in these driver genes have been widely demonstrated to cause hyperactivation of the PI3K signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…isotypique des centrocytes, diversifiant les fragments Fc des immunoglobulines et permettant l'expression des isotypes IgG, IgA et IgE. La différentiation terminale des centrocytes en cellules B mémoires ou en plasmablastes est également sous la dépendance de la signalisation du CD40, l'activation de cette voie orientant préférentiellement vers la cellule B mémoire et inhibant la génération de plasmocytes(126,127).Les lymphocytes B ont une capacité à initier le « priming » du lymphocyte T en agissant comme des CPA. Après leur prise en charge de l'antigène, les lymphocytes B ont un phénotype activé et une augmentation des molécules B7 et du CMH de classe II.…”
unclassified